MicroRNA-21 Mediates the Inhibiting Effect of Praziquantel on NLRP3 Inflammasome in Schistosoma japonicum Infection - Kong, Delong; Guo, Hongfei; Lu, Zhongkui; Cui, Jie (Frontiers in Veterinary Science, 2020)
Praziquantel (PZQ), a traditional helminthicide drug, has been shown to exert an anti-inflammatory effect on splenomegaly induced by schistosomiasis via regulating macrophage polarization. Meanwhile, miR-21 has been demonstrated to control macrophage polarization. However, the role of miR-21 in the regulation of macrophage polarization by PZQ in schistosomiasis is still unclear. In the present study, we found that M1-type macrophages were the predominant splenic macrophages in chronic schistosomiasis, and NLRP3 inflammasome-related molecules were up-regulated. PZQ inhibited NLRP3 inflammasome in M1 macrophages and reduced the expression of miR-21. Furthermore, using the methods of quantitative real-time PCR and transfection, the downregulation of NLRP3/IL-1β by PZQ in M1 macrophages were reversed by miR-21 overexpression. These results indicated that miR-21 was involved in the inhibiting effect of PZQ on activation of NLRP3 inflammasome. Moreover, miR-21 might target Smad7 to mediate the anti-inflammatory effect of PZQ in polarized macrophages. This study provides an in-depth mechanism of PZQ in the treatment of schistosomiasis.